Predicting the impact of transient voltage suppressor used for ESD protection on the low noise amplifier. (July 2021) - Mengxia, Zhou; Yang, Zhao; Cheng, Zhang; Xingfa, Liu; Xianqiang, Wu; Yiqun, Sun; Wei, Yan
Abstract: Low noise amplifiers (LNAs) are highly susceptible to electro-static discharge (ESD) events as they are directly connected to the antennas, therefore transient voltage suppressor (TVS) are often used as protective devices for ESD. In the radio frequency (RF) band, the parasitic parameters of TVS can heavily influence the performance of the functional circuit. The input impedance of the LNA can be disturbed and hence a loss of gain and work performance is the result. In this paper, a novel model of TVS is proposed to predict the impact of TVS on the LNA, which can illustrate the performance of TVS under the no-ESD-occurrence or ESD-occurrence state. The parasitic parameters of TVS is extracted by self-organizing migrating algorithm (SOMA). The gain of LNA with TVS is studied under no-ESD-occurrence state and the ESD protection characteristics of TVS are analyzed under ESD-occurrence state, which can provide a reference for the performance estimation and compensation of the LNA or other electrical equipment.